2022
DOI: 10.3390/ijerph19031306
|View full text |Cite
|
Sign up to set email alerts
|

Match Physical and Physiological Response of Amateur Soccer Referees: A Comparison between Halves and Match Periods

Abstract: The aim of this paper was to examine the differences in the external and internal load in amateur match officials between the 1st and 2nd half and among different 15 min periods. Twenty-three field referees (FRs) and 46 assistant referees (ARs) from the Spanish División de Honor participated in this study. Match external and internal loads were monitored showing that FRs recorded a lower Powermean, Speedmean, Cadencemean and Stiffnessmean (p < 0.05; d = 0.52 to 0.57) during the 2nd half and they also record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
(62 reference statements)
2
0
0
Order By: Relevance
“…While the findings have been mixed in the existing literature with respect to these variables, there have been some studies that demonstrated that physical responses were reduced in the 2nd half [ 25 , 38 ], as was the case for the World Championship in this study. More recent studies have shown that there were no differences in the distance covered between the 1st and 2nd halves [ 13 , 29 , 30 , 39 ], which is consistent with what is reported in the total values of the observations in this study. The negative influence of eligible impairments in footballers with CP have been extensively studied showing diminished physical performance as compared to footballers without CP [ 2 , 9 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While the findings have been mixed in the existing literature with respect to these variables, there have been some studies that demonstrated that physical responses were reduced in the 2nd half [ 25 , 38 ], as was the case for the World Championship in this study. More recent studies have shown that there were no differences in the distance covered between the 1st and 2nd halves [ 13 , 29 , 30 , 39 ], which is consistent with what is reported in the total values of the observations in this study. The negative influence of eligible impairments in footballers with CP have been extensively studied showing diminished physical performance as compared to footballers without CP [ 2 , 9 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…International games place demands on acceleration and deceleration actions highlighting that referees must be physically prepared to keep up with the game at any level of international play [ 12 ]. Interestingly, the obtained results in maximum speed (22.04 ± 2.69 km/h) were similar to those described by regular football referees, registering ~20.86 km/h [ 30 ], ~25.47 km/h [ 31 ], and ~19.40 km/h [ 32 ]. However, lower short-term actions were presented in CP football referees as compared to the performance of referees in regular football which might be due to the specific characteristics, the field size, and the demands of the para-sport.…”
Section: Discussionsupporting
confidence: 85%